1992
DOI: 10.1002/eji.1830220726
|View full text |Cite
|
Sign up to set email alerts
|

Induction of homotypic T cell adhesion by triggering of leukocyte function‐associated antigen‐1α (CD11a): differential effects on resting and activated T cells

Abstract: The leukocyte integrin LFA-1 (CD11a/CD18) plays a key role in many adhesive interactions involving cells of the immune system. Recently, it has been shown that LFA-1 is not only involved in cell adhesion, but that stimulation of LFA-1 can also contribute to cell activation. We now demonstrate that triggering of LFA-1 on T lymphocytes by monoclonal antibodies (mAb) against the LFA-1 alpha chain, but not against the LFA-1 beta chain, promotes cell adhesion. Induction of homotypic adhesion was only observed in T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Other cell surface antigens have been reported to upregulate LFA-1 activity when bound by the corresponding specific mAb, all of them presumably are signal transducer molecules able to activate the metabolic pathways involved in LFA-1 regulation [lo, 11,28,33,341. Different potentially overlapping molecular mechanisms may underlie HPlN-induced adhesion including: (a) a conformational change in LFA-1 as described for other integrins [3] and proposed for LFA-1 [32]; (b) a clustering of the molecule on the cell surface accounting for the facilitation of the adhesion process; c) a signal transduced by LFA-1 able to self-regulate its functional properties; this possibility is supported by the fact that HPlN mAb induced an increase in (Ca*+)i. Interestingly, HPlN brightly stained but failed to aggregate fresh unstimulated NK and Tcells; these data pointed out that lymphocytes required a preactivation to respond to the mAb, and are in agreement with other recent observations [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other cell surface antigens have been reported to upregulate LFA-1 activity when bound by the corresponding specific mAb, all of them presumably are signal transducer molecules able to activate the metabolic pathways involved in LFA-1 regulation [lo, 11,28,33,341. Different potentially overlapping molecular mechanisms may underlie HPlN-induced adhesion including: (a) a conformational change in LFA-1 as described for other integrins [3] and proposed for LFA-1 [32]; (b) a clustering of the molecule on the cell surface accounting for the facilitation of the adhesion process; c) a signal transduced by LFA-1 able to self-regulate its functional properties; this possibility is supported by the fact that HPlN mAb induced an increase in (Ca*+)i. Interestingly, HPlN brightly stained but failed to aggregate fresh unstimulated NK and Tcells; these data pointed out that lymphocytes required a preactivation to respond to the mAb, and are in agreement with other recent observations [35].…”
Section: Discussionsupporting
confidence: 92%
“…I n line with this is an increasing number of data suggesting an active role of LFA-1 in leukocyte activation . These phenomena are thought to involve phosphoinositide turnover and Ca2+ signaling [21], and t o be associated to cytoskeletal rearrangements [35,40]. We have observed that H P l N reproducibly triggered a transient increase in (Ca2+)i highly enhanced upon cross-linking of t h e antibody with an anti mouse IgG serum, suggesting that variation in (Ca2+)i might be one of the signals accounting for the costimulation of TNFa production, and for the induction of the homotypic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…It also acts as a costimulatory signal in T-cell interactions. 33 Two other surface activation receptors are CD69 and CD71. Activation-induced molecule (CD69) is present on activated but not resting T cells, and appears relatively early after T-cell activation.…”
Section: Pharmacology Of Cnis In T Cellsmentioning
confidence: 99%
“…Human peripheral blood obtained from healthy donors was used for isolation of peripheral blood mononuclear cells (PBMC) by density gradient centrifugation, using Ficoll‐Paque (Pharmacia Biotech, Uppsala, Sweden). T lymphoblasts were generated by culturing PBMC for 5–7 days in the presence of soluble OKT3 (mAb anti‐CD3) and of a cytokine mixture, that was obtained from activated PBMC, as described, 28 using RPMI culture medium (RPMI‐1640 supplemented with 10% heat‐inactivated fetal calf serum, 100 IU/ml penicillin, 100 µg/ml streptomycin, and 2 m m glutamin). The human Th0 cell clone ACC6 (kindly provided by Dr M. L. Kapsenberg, Amsterdam, the Netherlands), was stimulated every 14 days by allogeneic feeder cells and phytohaemagglutinin, as described, 29 and cultured in Iscove's modified Dulbecco's medium (Gibco BRL Life Technologies, Paisley, UK), supplemented with 10% heat‐inactivated normal human serum, 25 U/ml recombinant IL‐2 (Eurocetus, Amsterdam, the Netherlands), 100 IU/ml penicillin, 100 µg/ml streptomycin and 2 m m glutamin.…”
Section: Methodsmentioning
confidence: 99%